Princess Jellyfish. 04 - Higashimura, Akiko (Kodansha Comics, 2017)
"The night of the fashion show for Tsukimi and Kuranosuke's Jelly Fish brand has finally arrived. They pulled out all the stops to make Amamizu-kan into an enchanting wonderland -- even Mayaya has transformed into a chic model! The show brings some much-needed attention to the retro building, but will the exposure be enough to save the Amars and their home? When their fashion line becomes a hit success, the girls scramble to satisfy their customers. With the help of their new colleague Nisha, a savvy Indian expat who knows all about the textile industry, they just might make it work! ... But is Tsukimi ready to leave her quiet life behind for good?" -- Back cover.